An Ivestigation of Dividend Policy in the UK market - ZHANG, NA (2009)
Abstract This paper study the dividend policy of 258 firms listed on the London Stock Exchange during the period 1993-2008. The study examines the determinants that drive the dividend policy of UK firms. Moreover, this study tests whether the dividend policy in the UK market is stability or not. To find out the determinants of dividend policy, static panel data model which based on seven variables have been performed. First, firm growth and investment opportunities can be seen as a determinant, even if it is not significant affecting dividend policy. Furthermore, large size and profitable firms can afford high cash flows and thus pay high dividends. In addition, information asymmetries between inside managers and outside shareholders, taxation and financial leverage negatively impact the dividend policy. To answer the second question, Lintner‟s model is used in a dynamic panel data. The results demonstrate the stability of dividend policy and UK firms depend upon current earnings and previous dividends. However, current dividends are more sensitive to current earnings than past dividends